Can the post-colonial be post-religious? Reflections from the secular metropolis - Viefhues-Bailey, Ludger H. (Critical research on religion, 2015)
If, following Masuzawa, Fitzgerald and others we assume that "the religious" is a category produced by Western colonial regimes in tandem with that of "the secular," then consequently the post-secular would need to be post-religious, as well. Here I demonstrate how in one metropolitan case, Germany, the religious and secular divide is evoked to produce a particular exclusivist narrative of national identity. A substantial part of German civil society, media, and legal establishment mobilize an imagined culturally Christian vision of Germany in order to exclude from public visibility and political participation German born Muslims of Turkish descent. The colonial twin categories of secular-religious still operate in the shaping of the German polity. Decolonizing it would thus require not only to enter a post-secular dialogue with religious presentations in the public sphere, as Habermas contends; rather a post-secular polity would require the post-religious.